Identification and expression analysis of putative NLR genes in avocado, Persea americana, during infection by the oomycete, Phytophthora cinnamomi - Van den Berg, Noelani (University of Pretoria, 2022)
Dissertation (MSc (Genetics))--University of Pretoria, 2021.